The effects of backwards running training on forward running economy in trained males - Ordway, J. D.; Laubach, L. L.; Vanderburgh, P. M.; Jackson, K. J. (The Journal of Strength and Conditioning Research, 2016)
Backwards running (BR) results in greater cardiopulmonary response and muscle activity compared with forward running (FR). BR has traditionally been used in rehabilitation for disorders such as stroke and lower leg extremity injuries, as well as in short bursts during various athletic events. The aim of this study was to measure the effects of sustained backwards running training on forward running economy in trained male athletes. Eight highly trained, male runners (26.13 ± 6.11 years, 174.7 ± 6.4 cm, 68.4 ± 9.24 kg, 8.61 ± 3.21% body fat, 71.40 ± 7.31 ml/kg/min) trained with BR while harnessed on a treadmill at 161 m·min-1 for 5 weeks following a 5-week BR run-in period at a lower speed (134 m/min). Subjects were tested at baseline, postfamiliarized, and post-BR training for body composition, a ramped VO2max test, and an economy test designed for trained male runners. Subjects improved forward running economy by 2.54% (1.19 ± 1.26 ml/kg/min, p = 0.032) at 215 m/min. VO2max, body mass, lean mass, fat mass, and % body fat did not change (p > 0.05). Five weeks of BR training improved FR economy in healthy, trained male runners without altering VO2max or body composition. The improvements observed in this study could be a beneficial form of training to an already economical population to improve running economy.